Sharing Management of COVID-19 in America as well as Public Health Centers and Primary Clinics in Indonesia - Siti Marlina; Hari Kusnanto; Mark Alan Graber (Faculty of Medicine, Public Health, and Nursing, 2022)
Since the Coronavirus-2019 (COVID-19) was declared by the World Health Organization (WHO) as a pandemic on March 11, 2020, and then Indonesia declared COVID-19 a national disaster on March 14, 2020, COVID-19 cases in Indonesia and the world have increased rapidly. Puskesmas and clinics are at the forefront of handling and preventing the transmission of COVID-19. Puskesmas and clinics must prepare their own resources and service protocols in order to serve the community without neglecting the safety and health of patients and health workers from the risk of transmission of COVID-19. Health workers meet with patients and visitors to health facilities every day, sometimes even with inadequate personal protective equipment (PPE), so they are very much at risk of being exposed to COVID-19, from patients or vice versa. With the increase in COVID-19 cases, a comprehensive effort is needed in case management and efforts to break the chain of transmission and keep health workers protected in conducting their duties. Modification of health service facilities in Puskesmas and clinics, changes in service flow, standard operating procedures for health services must be adjusted by paying attention to the safety of health workers and patients/visitors to avoid COVID-19 transmission. Preparedness of Puskesmas and clinics in facing the COVID-19 pandemic should be done by strict management according to the patient's condition by paying attention to PPE principles, conducting strict surveillance of suspected and positive COVID-19 cases, case reporting system within 1x 24 hours to the District/City Health Office, conducting epidemiology investigations and providing risk communication to the community as well as improving networks with stakeholders, across sectors and local community leaders.